Influence of Socio-economic factors on utilization of sanitation facilities by women in Mukuru Kwa Reuben informal settlement in Nairobi County - Kariuki, Teresia Mucia; Kagendo, Dorothy; Kaimuri, Maryjoy (African Journal of Science, Technology and Social Sciences, 2024)
Accessing basic sanitation services is still a challenge in slums and sanitation needs of some groups specifically women at times remain unmet. This study assessed the socio-economic factors that influence the utilization of sanitation facilities by women at Mukuru Kwa Reuben, Kenya. The study targeted women aged 18 and above who consented. The Sample size was 395 women at Mukuru Kwa Reuben. Clustered and simple random sampling techniques were utilized to select the study participants. The data collection tools were questionnaires, focus group discussions and observation. Descriptive and inferential statistics were utilized for quantitative data analysis. Study findings are presented in tables. Qualitative data was analyzed thematically and presented in form of narratives. Results from the analysis showed that majority of the most common sanitation facility at Mukuru kwa Reuben was container based (51.0%). The socioeconomic factors that significantly influenced the utilization of sanitation facilities by women were cultural beliefs (r=-0.613, p=0.000), that had a strong negative association with utilization, education level (r=0.593, p=0.000), had a strong positive association with utilization, and economic status (r=0.466, p=0.000), had a moderate positive association with utilization. This study highlights persistent challenges in slums, particularly for women's access to sanitation. Socio-economic factors significantly influence sanitation facility utilization by women in Mukuru Kwa Reuben, Kenya. There is need for holistic interventions to address beliefs, education, and economic status for improved sanitation practices.